Effective construction project communications - Freeman, John (Department of Mechanical Engineering, 2016)
Large construction projects involve numerous participants, many of whom do not participate for the entire duration of the project. Participants often come from very different cultural and linguistic backgrounds. In the case of many large projects, the levels of education of these participants also vary widely, from graduate professionals to labourers with only a basic education. For a project to be developed, executed and handed over to the owner efficiently, the activities and delivered outputs of the project participants need to be coordinated. This requires effective communication to and feedback from all stakeholders. Project communication systems therefore have to take into account the differing backgrounds and information requirements of the participants. The execution of a high proportion of construction projects is negatively affected due to ineffective project communications. This gives rise to the concern that construction project communications can contribute to late or inappropriate actions by participants that can negatively affect project delivery. This informed the research question: "How can project team communication systems be optimised to ensure that all stakeholders have all the information and understanding required to function efficiently, effectively and timeously?" This research study sets out to answer this question. The first objective of this study was to identify the main factors that cause project communications to be ineffective. The second objective was to develop a theory relating to effective project communications systems that could be useful in developing practical solutions to project communication problems.